Facility-Based Surveillance Activities for COVID-19 Infection and Outcomes among Healthcare Workers in a Nigerian Tertiary Hospital - Ogboghodo, Esohe O.; Osaigbovo, Iriagbonse I.; Obarisiagbon, Otaniyenuwa O.; Okwara, Benson U.; Obaseki, Darlington E.; Omo-Ikirodah, Orezimena T.; Ehinze, Ewere S.; Adio, Funmilola; Nwaogwugwu, Joy C.; Eseigbe, Efeomon F. (The American journal of tropical medicine and hygiene, 2021)
COVID-19 in healthcare workers (HCWs) can result in nosocomial transmission, depletion in available workforce, and enhanced community transmission. This article describes surveillance for COVID-19 in HCWs at a tertiary healthcare facility, and documents the outcomes. A descriptive cross-sectional study of all HCWs identified from surveillance for COVID-19 from March 31 to August 31, 2020 was conducted. Healthcare workers were categorized as high risk and low risk using an adapted WHO Risk Assessment tool. Nasopharyngeal and oropharyngeal swab specimens obtained from high-risk subjects were tested by a reverse transcriptase PCR method. Data were analyzed with IBM SPSS version 25.0 software (IBM SPSS Statistics for Windows, Version 25.0, Armonk, NY), and results were presented as frequencies and percentages. The level of significance was set at P < 0.05. During 5 months of surveillance, 1,466 HCWs with a mean age of 38.1 ± 9.7 years were identified as contacts. On risk assessment, 328 (22.4%) were adjudged high risk. High risk was associated with increasing age ( P < 0.001), male gender ( P = 0.001), and nonclinical staff ( P = 0.002). Following testing, 78 (5.3%) in the high-risk category were confirmed to have COVID-19. There was no record of COVID-19 in HCWs adjudged low risk. Forty-four (56.4%) cases were epidemiologically linked to the community, 20 (25.7%) to patients, and 14 (17.9%) to another HCW. Surveillance and risk assessment are crucial to COVID-19 response in healthcare facilities and revealed HCW infections with predominantly nonoccupational epidemiological links in this study.